2016
DOI: 10.1021/acs.nanolett.5b04540
|View full text |Cite|
|
Sign up to set email alerts
|

Anisotropic Electron-Photon and Electron-Phonon Interactions in Black Phosphorus

Abstract: Orthorhombic black phosphorus (BP) and other layered materials, such as gallium telluride (GaTe) and tin selenide (SnSe), stand out among two-dimensional (2D) materials owing to their anisotropic in-plane structure. This anisotropy adds a new dimension to the properties of 2D materials and stimulates the development of angle-resolved photonics and electronics. However, understanding the effect of anisotropy has remained unsatisfactory to date, as shown by a number of inconsistencies in the recent literature. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
457
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(497 citation statements)
references
References 28 publications
35
457
2
Order By: Relevance
“…Angle-dependent Raman scattering measurements of these samples show strong anisotropy in the 214 cm −1 peak intensity with clear twofold symmetry, as seen in recent reports [9,17,18].…”
Section: Methodssupporting
confidence: 82%
“…Angle-dependent Raman scattering measurements of these samples show strong anisotropy in the 214 cm −1 peak intensity with clear twofold symmetry, as seen in recent reports [9,17,18].…”
Section: Methodssupporting
confidence: 82%
“…Furthermore, polarized Raman characterization was implemented to explore the polarization dependence due to the reduced symmetry of the orthorhombic phase. The authors inspected that the orthorhombic phase SnS nanosheets exhibit strong anisotropic Raman response similar with black phosphorous150 and ReS 2 151, 152, 153, 154. The parallel‐polarization configuration strongly suggests that the A 1g mode (190.7 cm −1 ) can be employed to detect crystallographic orientation of the SnS flakes because of the A 1g mode reaches the maximum as illumination light polarization is parallel to armchair direction of the SnS flakes, which may also exist in other group IV orthorhombic phases such as SnSe, GeS, and GeSe.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…In addition, it was recently demonstrated that the exciton binding energy depends on the type of substrate due to environmental effects on the dielectric constant [22]. Phosphorene also shows a strong optical anisotropy for light polarization in the two high symmetry directions which is related to the large anisotropy of the electron effective masses [21,23,24,28,29].…”
Section: Introductionmentioning
confidence: 99%